Critical Dissolved Oxygen Tolerances of Whirling Disease-Resistant Rainbow Trout. (1st October 2016) - Fetherman, Eric R.; Wardell, Jonathan A.; Praamsma, Chris J.; Hura, Marta K.
Abstract: A low concentration of dissolved oxygen (DO) is commonly the limiting factor in fish culture systems. Hypoxia tolerance in Rainbow Trout Oncorhynchus mykiss can be affected by both history of domestication and growth rate. As such, selecting strains for specific characteristics such as growth rate or disease resistance could potentially affect DO tolerance, making culture difficult. Here we used two experiments to examine the differences in tolerance to lower DO concentrations among four Rainbow Trout strains and crosses selected for resistance to whirling disease Myxobolus cerebralis . The first experiment examined differences in critical DO concentrations of fry (≥73 mm total length [TL]) when exposed to rapid decreases in DO at 30, 60, 90, and 120 d postswim-up. In addition, since formalin is a common chemical used in aquaculture to treat for external parasites, the effect of exposure to formalin on tolerance to low DO was evaluated. The second experiment evaluated critical DO concentrations among four strains and crosses exposed to a prolonged decrease in DO at age 7 months (averaging 178 mm TL). Formalin exposure had an effect on low-DO tolerance, with DO concentrations that resulted in a loss of equilibrium decreasing with an increase in formalin concentration. In addition, low-DO tolerances were diminished with an increase in fish size, with larger fish losing equilibrium at higher DO concentrations. Differences in DO concentrations resulting in loss of equilibrium and mortality were evident among the strains and crosses in the second experiment. This experiment demonstrated that DO concentrations must be below 2.0 mg/L before loss of equilibrium is observed. However, if fish are soon returned to well-oxygenated water, losses can be minimized. Additionally, other hatchery practices that compromise hypoxia tolerance may increase mortality more quickly following low-DO exposure, and care should be taken to correct low-DO issues shortly after loss of equilibrium is observed. Received February 17, 2016; accepted May 31, 2016